Pengaruh Kompetensi, Kerjasama Tim dan Motivasi Kerja Terhadap Kinerja Karyawan di PT Budi Jaya Teknik - Nony Noor Chamimy; M. Syamsul Hidayat; Kasnowo Kasnowo (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
An organization's ability to achieve its objectives largely depends on the quality of its human resources, which makes employee performance a critical area requiring close attention. This research was carried out to explore how competency, teamwork, and work motivation relate to employee performance at PT Budi Jaya Teknik, a mechanical-electrical service company also serving as a PLN vendor in the Jombang region. An associative approach with quantitative methods was applied in this study, involving all 31 employees as respondents through a total sampling technique. Data were gathered using a five-point Likert-scale questionnaire, which was subsequently analyzed with SPSS version 26. The analytical procedure covered validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and calculation of the coefficient of determination. On a partial basis, competency and teamwork were found to exert a positive and meaningful influence on employee performance, whereas work motivation did not show a notable effect. Nevertheless, when examined simultaneously, all three variables were confirmed to have a significant influence on employee performance. The Adjusted R Square value of 0.799 indicates that competency, teamwork, and work motivation together account for 79.9% of the variation in employee performance, while the remaining 20.1% is attributable to other variables not covered in this study.